Evaluación del potencial de radiación solar y geotérmico de baja entalpía en el centro educativo “latinoamericano” de la ciudad de Ambato, provincia de Tungurahua, durante el período 2014 – 2015. Propuesta de implementación de un sistema energético híbrido solar y geotérmico para uso de consumo eléctrico y calefacción. - Ortiz Bonilla, Fernando Javier (2016)
The present research was made mainly for study initial evaluation study of the solar photovoltaic captation and low enthalpy geothermal potential power, in this case to establish implementation projections based on availability of resources inside the site where is built the “Latinoamericano” education center, located in Ambato, Tungurahua. For the entire comprehension of the phenomenon, the researcher realized a theoretical research, in addition of the research background, along with a methodological structure and the use of special instrumentation to conceive the main idea of the energetic catchment previously established. Finally, there is elaborated a proposal, selecting the technology according to a parametric relation and a feasibility study according to their useful life in order to take decisions for the physical introduction of an hybrid electric and heating system.